Reliability and Criterion Validity of the Assess2Perform Bar Sensei - George K. Beckham; Danielle K. Layne; Steven B. Kim; Eric A. Martin; Benjamin G. Perez; Kent J. Adams (MDPI AG, 2019)
The Assess2Perform Bar Sensei is a device used to measure barbell velocity for velocity-based training that has not yet been validated. The purpose of this study was to determine criterion validity and reliability of the Assess2Perform Bar Sensei in barbell back squats by comparing it against the GymAware PowerTool, a previously validated instrument. Sixteen injury-free, resistance-trained subjects (eleven males and five females) were recruited. Subjects were tested for their back squat one repetition maximum (1RM). Then, on two separate days, subjects performed two sets of three repetitions at loads of 45%, 60% and 75% 1RM. The GymAware PowerTool and Bar Sensei were attached to the barbell in similar locations for concurrent collection of mean concentric velocity (MCV) and peak concentric velocity (PCV). The Bar Sensei and PowerTool showed generally fair to poor agreement for MCV and PCV when subjects lifted 45% of 1RM (intraclass correlation;ICC 0.4−0.59), and they showed poor agreement when subjects lifted 60% and 75% of 1RM (ICC 0.3−0.4). Inter-repetition/within-set reliability for the Bar Sensei ranged between ICC = 0.273−0.451 for MCV and PCV compared to the far more reliable PowerTool (ICC = 0.651−0.793). Currently, the Bar Sensei is not a reliable or valid tool for measuring barbell velocity in back squats.